Diabetes-related distress and psychological burden in patients with type 1 and type 2 diabetes – the role of child maltreatment, personality functioning, and epistemic trust: findings from a German clinical inpatient sample - Zara, Sandra; Ullrich, Imogen Carla; Leveling, Anna Maria; Saretzki, Friederike Gisela Genoveva; Schmitz, Jana; Eckhard, Michael; Kruse, Johannes; Kampling, Hanna; Justus Liebig University Giessen (My University, 2025)
Patients with diabetes exhibit high frequencies of psychological burden and diabetes-related distress. Child maltreatment has been independently linked to both diabetes and psychological burden. We aimed 1) to explore the association between child maltreatment and diabetes-related distress, and between child maltreatment and psychological burden, and 2) to investigate the mediating role of personality functioning (psychological abilities with regard to the self and others) in this association. We included epistemic trust (openness for social learning) and its impairments mistrust (the tendency to consider information sources as unreliable or ill-intended) and credulity (lack of vigilance and discrimination between trustworthy and untrustworthy information) as covariates.
Keywords: ddc:610